2016
DOI: 10.5966/sctm.2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Functional Definition of Endothelial Progenitor Cells: A Molecular Perspective

Abstract: Notch signaling driving the quiescence of progenitors has been shown to be central to progenitor self‐renewal. This new molecular definition has tremendous translational consequences because progenitors have been shown to display greater vasculogenic potential. This molecular definition of endothelial progenitor cell (EPC) self‐renewal allows assessment of the quality of presumed EPC preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 56 publications
(66 reference statements)
1
42
0
Order By: Relevance
“…In this sense, endothelial progenitor cells (EPCs) have arisen as promising candidates for therapeutic applications pursuing tissue revascularization such as in CLI due to their assigned vascular regenerative properties [12]. Since their discovery in 1997 [13], many researchers have explored the potential of using EPCs in tissue engineering as an angiogenic source for vascular repairing [14,15], with many publications also focused on the controversy regarding isolation techniques as well as the definition of EPC phenotypes, presenting still a variety of results in terms of surface-based EPC markers [14,16,17]. In this regard, a consensus has been reached at least in the need to discriminate between two different populations of the so-called EPCs, depending on the differentiation status or their capability to form colonies [17][18][19][20]: early EPCs (eEPCs), also defined as circulating angiogenic cells (CACs) or myeloid angiogenic cells (MACs), and late outgrowth EPCs or endothelial colony-forming cells (ECFCs).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, endothelial progenitor cells (EPCs) have arisen as promising candidates for therapeutic applications pursuing tissue revascularization such as in CLI due to their assigned vascular regenerative properties [12]. Since their discovery in 1997 [13], many researchers have explored the potential of using EPCs in tissue engineering as an angiogenic source for vascular repairing [14,15], with many publications also focused on the controversy regarding isolation techniques as well as the definition of EPC phenotypes, presenting still a variety of results in terms of surface-based EPC markers [14,16,17]. In this regard, a consensus has been reached at least in the need to discriminate between two different populations of the so-called EPCs, depending on the differentiation status or their capability to form colonies [17][18][19][20]: early EPCs (eEPCs), also defined as circulating angiogenic cells (CACs) or myeloid angiogenic cells (MACs), and late outgrowth EPCs or endothelial colony-forming cells (ECFCs).…”
Section: Introductionmentioning
confidence: 99%
“…Fist pioneer investigations that confirmed being of special populations of the circulating cells with impressive angiogenic abilities were provided by Asahara et al 13 Using animal models of ischemia authors found sites of active angiogenesis with incorporated into its putative EPCs or angioblasts, which were further isolated from peripheral blood of animals and humans by magnetic bead selection on the basis of cell surface antigen expression. 14,15 These cells have demonstrated an high ability to differentiation onto an endothelial lineage in colonies in culture, and in animal studies these cells have been incorporated into active cores of neovascularization demonstrating impressive capability to attenuate angiogenesis and vascular function in vivo through differentiation into mature endothelial cells. 15,16 Taking into consideration the origin of these cells from bone marrow stem cells and human umbilical cord blood and that fact they may mobilize and migrate from bone marrow and differentiate into mature endothelial cells the population of these precursors were called EPCs.…”
Section: Progenitor Endothelial Cellsmentioning
confidence: 99%
“…14,15 These cells have demonstrated an high ability to differentiation onto an endothelial lineage in colonies in culture, and in animal studies these cells have been incorporated into active cores of neovascularization demonstrating impressive capability to attenuate angiogenesis and vascular function in vivo through differentiation into mature endothelial cells. 15,16 Taking into consideration the origin of these cells from bone marrow stem cells and human umbilical cord blood and that fact they may mobilize and migrate from bone marrow and differentiate into mature endothelial cells the population of these precursors were called EPCs. Later it has known that EPCs may transdifferentiate into cells with phenotype distinguished from mature endothelial cells, for example, smooth muscle cells of the media of vessels.…”
Section: Progenitor Endothelial Cellsmentioning
confidence: 99%
“…Notably, an attribute of a progenitor cells population is ability of them to self-renewal and multiple potentialities [26]. Sorting and identification of EPC populations, i.e.…”
Section: The Definition Of the Epcsmentioning
confidence: 99%
“…There is a large body of evidence regarding that the pro-and anti-inflammatory cytokines produced by numerous immune and antigenpresenting cells in HF are co-regulators of EPC activities through supporting oxidative stress and via direct stimulation of some intracellular signal systems (Akt/STAT3) [ [17][18][19] and thereby induce microvascular dysfunction [20]. However, poor abilities of EPCs to differentiation, migration, transformation, survival, as well as lowered number of circulating EPVs in peripheral blood in individuals at risk of HF and among patients with established HF with different phenotypes were determined in numerous studies [21][22][23][24][25][26]. Finally, the predictive and diagnostic role of EPC count and function in HF is not fully clear and requires to be reappraised in the future.…”
Section: Introductionmentioning
confidence: 99%